Analysis of Fundamental Motor Skills of Students Aged 7 to 9 Years in West Sumatra Province - Oktarifaldi Oktarifaldi (STKIP Pasundan Press, 2026)
Fundamental movement skills are the main element that determines a person's ability to engage in physical activity. This study aims to describe differences in students' basic movement skills based on ages group. This study design was descriptive using a cross-sectional approach. Fundamental motor skills were evaluated using the TGMD-2 instrument. The research subjects were elementary school students in grades 1, 2 and 3 in West Sumatra who were determined purposively with details (N=204; boys =102 and girls =102). The data were analyzed using the IBM SPSS statistics program version 25. The average Gross Motor Quotients (M=82.15, SD=10.5) was obtained and tended to decrease with age. Average Gross Motor Quotiens of the 7 year age group (M=85.79 SD=7.8), the 8 year age group (M=82.31 SD=10.41) and the 9 year age group (M=78.34 SD=11.7). The results of the one-way ANOVA test between age groups showed that there was a significant difference in the average GMQ of students (p value <0.05). In general, students' fundamental motor skills are below average, male students are superior to female students in all age groups